2020
DOI: 10.1016/j.ijpam.2019.09.003
|View full text |Cite|
|
Sign up to set email alerts
|

The prevalence of viral infections in children with cystic fibrosis in a tertiary care center in Saudi Arabia

Abstract: Introduction: Studies have shown that pulmonary exacerbations in cystic fibrosis (CF) patients are associated with respiratory viruses. The most common agent causing viral infections in patients with CF before the age of 3 years is respiratory syncytial virus. Objectives: To obtain the prevalence of the different types of viral infection in CF patients and to identify its relation with the type of bacterial infection, (CFTR) mutations and pulmonary func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
2
1
Order By: Relevance
“…Similarly, it was reported as the most common respiratory virus in exacerbations of CF in many other studies. 2,3,6,7 In our study, influenza A virus was detected in only 6.7% of patients although no one had a history of influenza vaccination. Similarly, a French study found that its prevalence was 9%.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Similarly, it was reported as the most common respiratory virus in exacerbations of CF in many other studies. 2,3,6,7 In our study, influenza A virus was detected in only 6.7% of patients although no one had a history of influenza vaccination. Similarly, a French study found that its prevalence was 9%.…”
Section: Discussioncontrasting
confidence: 56%
“…Wat et al 9 didn't find statistical differences between the viral and non-viral groups for bacteria isolation (p=0.909). Charles and 6 Also, Garcia et al 12 has shown that human metapneumovirus behaves similarly to respiratory syncytial virus in CF and leads to an increased risk of hospitalization and exacerbation.…”
Section: Discussionmentioning
confidence: 99%
“…17 Interestingly, c.3419T>A )p.Met1140Lys(, which accounted for 7.2% of the cases in this study, has been reported in only one patient in Saudi Arabia, and c.4124A>C )p.His1375Pro( )in 5.8% of our cases( has not been previously reported in Saudi patients with CF. 47 In addition, our study reports variants of the CFTR gene that have not been previously reported in the Saudi population. However, these variants have been reported or published in the literature in other Arab and American populations.…”
Section: Discussionmentioning
confidence: 57%